Pengaruh Inflasi, Indeks Pembangunan Manusia, Dan Upah Minimum Provinsi Terhadap Pengangguran Di Indonesia - Soeharjoto Soekapdjo; Mitha Rachma Oktavia (LPPM Universitas BSI, 2021)
Indonesia, which is part of Association of Southeast Asian Nations and Group of Twenty, participates in implementing sustainable economic development. There are still constraints in terms of macroeconomic development, such as employment which resulting in unemployment. This condition will affect the society and disrupt social and political stability. So it is necessary to conduct research related to unemployment.Purpose of this study is to analyze inflation effect, human development index, provincial minimum wage on unemployment in Indonesia. Used panel data regression method, with data from 33 provinces in Indonesia from 2015-2018. Unemployment is dependent variable with inflation, the human development index, and the provincial minimum wage as an independent variables. Accordance with the fixed effect model, results shown that inflation and human development index have a negative and significant effect on the unemployment in Indonesia, while the provincial minimum wage is not significant to the unemployment in Indonesia. To reducing unemployment, government can increasing their regions potentials, good regulations, and also society creativity and education.Keywords: Human Development Index, Inflation, Provincial Minimum Wage, Unemployment